UDDER TEAT MORPHOLOGY AND BODY MEASUREMENTS AND THEIR RELATIONSHIP WITH MILK YIELD AND MILKING TRAITS IN GIR COWS (Indian Journal of Animal Production and Management, 2013)
An investigation was undertaken to study the udder, teat and body measurements as affected by parity and their relationship with milk yield and milking traits in 100 Gir cows at Cattle Breeding Farm, JAU, Junagadh. Mean udder length, width and depth were found to be (cm) 45.99 ± 2.07, 20.51 ± 0.99 and 20.29 ± 1.04, respectively and were significantly (P < 0.01) affected according to different orders of lactations. Positive and significant correlations were observed among all the udder measurements. However, the correlation was significant among Udder length, Udder width and daily milk yield (kg) (P
Keywords: udder measurements; teat measurements; body measurements; parity; milk yield; milking traits; Gir cows